INTERDISCIPLINARY ANALYSIS OF CONSUMER BEHAVIOR THEORIES AND DECISION-MAKING FACTORS - Khalmurzayeva Naima Fatikhovna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article examines the main theories that explain how and why people make purchasing decisions. Various approaches are analyzed, including rational choice theory, psychoanalytic theory, Maslow's theory of motivation, behavioral and cognitive theories, as well as socio-cultural and emotional approaches. Special attention is paid to the influence of internal and external factors on consumer behavior, including motivation, emotions, social norms, and cognitive biases. The article highlights the importance of using an interdisciplinary approach in the study of consumer behavior and its application in marketing and business strategies